EVALUASI PENERIMAAN DAN PENGGUNAAN DALAM KEPUASAN PENGGUNA TERHADAP APLIKASI SIMLITABMAS UPN "VETERAN" JAKARTA MENGGUNAKAN PENDEKATAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Nursafira Khoirunniswah (2021)
With the development of technology and information science, the role of information systems in education is very important. The use of information systems in education not only supports teaching and learning activities, but all management activities. However, the application of information technology is not always successful. UPN "Veteran" Jakarta has implemented technology in every functional activity, one of which is the Simlitabmas application of UPN "Veteran" Jakarta which is intended for all permanent lecturers of UPN "Veteran" Jakarta to facilitate uploading of information data and important documents on research and community service. The purpose of this study is to determine the factors that most influence the intention and use of the Simlitabmas UPN "Veteran" Jakarta application in the Unified Theory of Acceptance and Use of Technology (UTAUT) model using PLS-SEM as a data analysis method. This research was conducted using quantitative methods by distributing questionnaires to 104 permanent lecturers of UPN "Veteran" Jakarta. In conclusion, it shows that users are satisfied with the performance expectations, social influences and facility conditions on the UPN "Veteran" Jakarta Simlitabmas Application. Meanwhile, the hypothesis of convenience expectations is rejected so that users are not satisfied with the convenience expectations of the UPN "Veteran" Jakarta Simlitabmas Application.